Bibliometric Analysis of Basella ssp. as an Antioxidant - Swastini Dewa Ayu; Martien Ronny; Fachiroh Jajah; Endro Nugroho Agung (BIO Web of Conferences, 2023)
The last ten years have seen the discovery of free radicals and their damaging impacts. Increasing exogenous antioxidant intake could reduce the damage caused by oxidative stress. Several plants have been shown to have antioxidant activity, and one such plant is BasellaI. It is high in phytochemicals which can act as antioxidants, and its consumption may help fight free radicals generated by the body. In particular, this plant is essential for stimulating normal wound healing response. To the best of our knowledge, no bibliometric analysis of published data on Basella as an antioxidant has been done. The goal of this study is to conduct a bibliometric analysis of the research on Basella’s antioxidant properties in the Scopus database using the VOSviewer and RStudio tools. There were 56 articles on Basella as an antioxidant according to the bibliometric analysis. The countries with the highest research output was India (27 documents), and the most productive institution was Chiang Mai University (15 documents). The most productive source was the International Journal of Pharmacy and Pharmaceutical Sciences. P. Giridhar had significant significant impact on papers on Basella as an antioxidant (H-index of 5). The most common keywords were “antioxidant” (859 occurrences with 1,340 total link strength) and “Basella alba” (606 occurrences with 1,048 total link strength). Findings from this data suggest the novelties of Basella as an antioxidant.